2020
DOI: 10.1039/c9ce01417a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent influenced synthesis of single-phase SnS2 nanosheets for solution-processed photodiode fabrication

Abstract: The effect of variant high boiling point solvent combinations in the synthesis and photo-sensing characteristics of tin disulfide (SnS2) thin nanosheets were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Further, the Raman spectrum is flat except for a peak slightly above 300 cm –1 . The latter is likely related to the amorphous SnS 2 film on the Si substrate (Figure b) since the A 1g peak of crystalline SnS 2 is found in this region . It is therefore unclear which SnS polymorph eventually develops on SnS 2 , but SEM indicates slow formation of isolated, flat grains of seemingly crystalline nature (Figure b).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, the Raman spectrum is flat except for a peak slightly above 300 cm –1 . The latter is likely related to the amorphous SnS 2 film on the Si substrate (Figure b) since the A 1g peak of crystalline SnS 2 is found in this region . It is therefore unclear which SnS polymorph eventually develops on SnS 2 , but SEM indicates slow formation of isolated, flat grains of seemingly crystalline nature (Figure b).…”
Section: Resultsmentioning
confidence: 98%
“…The latter is likely related to the amorphous SnS 2 film on the Si substrate (Figure 9b) since the A 1g peak of crystalline SnS 2 is found in this region. 45 It is therefore unclear which SnS polymorph eventually develops on SnS 2 , but SEM indicates slow formation of isolated, flat grains of seemingly crystalline nature (Figure 8b). It is worth noting that with further optimization of the SnS 2 deposition process and surface patterning, the strongly suppressed growth could be of interest for area-selective ALD of SnS.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The photosensitivity (P S ), responsivity ), quantum efficiency specific directivity are the vital parameters to investigate the photodiode/detector performance of the p-CuO@CuS/n-Si device. The photosensitivity (P S ) of the diode can be calculated from the following equation [ 53 ]. 100 here I ph and I d are related to current under photo & dark environments.…”
Section: Resultsmentioning
confidence: 99%
“…Upon mixing with OAc, the slower nucleation and growth steps affected the particle shape, leading to flat and well-defined edges. 223 In fact, it has been reported that the ratio of OAm cis to trans isomers and the amount of OAc can also influence the size and thickness of tin sulfide nanosheets, as well as their crystal structure (α-SnS or π-SnS). For example OAc was reported to form a highly ordered monolayer on the (100) surfaces of PbS, and thus suppressing an increase in the nanosheet thickness.…”
Section: Metal Chalcogenidesmentioning
confidence: 99%